Sintren sebagai Media Dakwah Islam di Cirebon: Perspektif Budaya dan Agama - Nurhikmah, Alfin (Medan Resource Center, 2023)
This research discusses the role of Sintren art in the spread of Islam in the northern coastal regions of Central and West Java during the period of Islamization. The aim is to delve into the contribution of Sintren art as a tool for Islamic preaching, with a focus on the implicit religious messages conveyed in its performances. This study employs methods of analyzing dance movements, song lyrics, and musical instruments used in Sintren performances. The results reveal that Sintren art plays a significant role in facilitating the spread of Islam, with religious messages implicit in these performance elements. The conclusion of this research is that similar to other traditional arts like wayang, Sintren art has played a role in aiding the understanding and acceptance of Islam by the people of that era and has contributed to the preservation of ancestral cultural heritage.